A Survey on EMG Biofeedback System - Shakya, Hemlata; Sharma, Shiru (Science and Engineering Research Support Society, 2015)
In this paper describe a new technology of placing electrodes on user’s muscle recording the electrical activity which is called as electromyography. EMG is an instrument that recording the electrical activity of the muscles. It is a diagnostic procedure to assess the health of muscles and the nerve cells that control them. In this paper reviews relating to the biofeedback used in physical rehabilitation. The physiological systems of the body which can be measured to provide biofeedback are the musculoskeletal system. EMG biofeedback useful in both musculoskeletal and neurological rehabilitation.
Keywords: Biofeedback; Electromyography; Muscles